Empirical Identification of Time Preferences: Theory and An Illustration Using Convex Time Budgets - Antoine Bommier; Bruno Lanz (University of Neuchâtel, Institute of Economic Research (IRENE), 2017)
We develop a simple theoretical framework that identifies time preferences without relying on a particular utility function. Our empirical strategy requires observations about intertemporal consumption allocation decisions made under varying relative prices, and seeks to approximate the marginal rate of substitution of consumption at different dates along a constant consumption path. Doing so, we emphasize the importance of measuring the curvature of the intertemporal utility function (or willingness to substitute consumption across time). We illustrate our approach with data derived from the convex time budget procedure of Andreoni and Sprenger (AER, 2012).
Keywords: D03; D12; D91; E61; 330; Intertemporal choice; Discounting behavior; Intertemporal substitution; Discounted utility model; Convex budgets